Extracellular matrix remodeling and transforming growth factor-β signaling abnormalities induced by lamin A/C variants that cause lipodystrophy - Le Dour, Caroline; Wu, Wei; Béréziat, Véronique; Capeau, Jacqueline; Vigouroux, Corinne; Worman, Howard J (Journal of lipid research, 2017)
Mutations in the lamin A/C gene encoding nuclear lamins A and C (lamin A/C) cause familial partial lipodystrophy type 2 (FPLD2) and related lipodystrophy syndromes. These are mainly characterized by redistribution of adipose tissue associated with insulin resistance. Several reports suggest that alterations in the extracellular matrix of adipose tissue leading to fibrosis play a role in the pathophysiology of lipodystrophy syndromes. However, the extent of extracellular matrix alterations in FPLD2 remains unknown. We show significantly increased fibrosis and altered expression of genes encoding extracellular matrix proteins in cervical subcutaneous adipose tissue from a human subject with FLPD2. Similar extracellular matrix alterations occur in adipose tissue of transgenic mice expressing an FPLD2-causing human lamin A variant and in cultured fibroblasts from human subjects with FPLD2 and related lipodystrophies. These abnormalities are associated with increased transforming growth factor-β signaling and defects in matrix metalloproteinase 9 activity. Our data demonstrate that lamin A/C gene mutations responsible for FPLD2 and related lipodystrophies are associated with transforming growth factor-β activation and an extracellular matrix imbalance in adipose tissue, suggesting that targeting these alterations could be the basis of novel therapies.